Kazakhstan tourist brand сreation – from country to region! (Journal of Economic Research & Business Administration, 2018)
The current stage in the development of the world tourism market shows that competition betweentourist destinations regarding investments, information, transport and tourist flows, environmental, economic,social and cultural projects, ideas and, of course, specialists with value in the labor market isbecoming more acute. Further, according to experts’ forecasts, interregional competition will intensify,and in the best position will be those of the tourist regions that not only possess the claimed regionalresources, but also will be able to use them with benefit for their development. In the conditions of suchinterregional competition, the role of the formation of one’s own individuality, allowing the tourist destinationto attract and increase resources for its development, increases. Thus, the relevance of the themeof creating a tourism brand is determined by a new stage in the development of society, accompaniedby the growth of the influence of mass media and the formation of brand perception as a new intangibleasset creating added value and a new competitive advantage. The creation of a tourist brand is, in asense, also a requirement of time, determined by the growing strength of market relations in the contextof globalization.The purpose of the article is to demonstrate the primary role of the construction of the country’stourism brand in the development of the Kazakhstan tourist industry. The authors provide a multi-levelsystem of marketing strategy for promoting the country’s tourism brand at the level of the country,region and product; suggest specific steps and mechanisms for its creation; give examples of foreignpractice; outline the vision of the country’s tourism product line at the regional level and with a singlelink to the common brand.The construction of the country’s tourism brand and high-quality effective implementation of themarketing strategy for its promotion will increase the flow of foreign tourists and bring the industry to amore developed level.